(untitled) (Mūzikas akadēmijas raksti, 2024)
Social activity was one of the most significant phenomena that characterized the first decade of Latvia’s state formation. Musicians also took part in this process, as evidenced by the founding of many musicians’ associations in the 1920s. This article attempts to introduce one of the oldest and most thorough musicians’ associations during the first period of Latvia’s Independence – the Latvian Musicians’ Society, its main activity fields, and their special concert campaign “Musicians Day”. The article is based on the author’s bachelor’s thesis, which initiates a new research area in Latvian Musicology, as this is the first in-depth archival study of music societies in Latvia.The Latvian Musicians’ Society (Latvijas Mūziķu biedrība) was founded at the end of 1922. It operated in very challenging and rapidly changing times in the history of Latvia. In 1919, the first national music institutions had just been founded (the Latvian National Opera and the Latvian Conservatory). The year 1925 marked the beginning of the Latvian public broadcaster (the Riga Radiophone). Towards the end of the decade, Latvian musicians were affected by the popularity of jazz and dance music as well as by the advent of sound films. In the 1930s, musicians struggled with the consequences of the economic crisis. However, the development of the Latvian democratic movement was interrupted in 1934 when Kārlis Ulmanis established an authoritarian regime. However, the Latvian Musicians’ Society was not eliminated. It continued to operate under the new forms of centralized management. At first, in 1936, the Latvian Musicians’ Society was included in the Latvian Chamber of Labor (Darba kamera) as a Musicians’ Union. But later, in 1938, it was added to the Latvian Chamber of Writing and Art (Rakstu un mākslas kamera). The Music Section of this last Chamber established a new music association called the Latvian Music Society to which the Latvian Musicians’ Society and last remaining music associations were added in 1939. However, the Latvian Music Society existed for a very short time – it was interrupted by the occupation of Latvia in 1940, after which the society was transformed into the Latvian SSR Musicians’ Union.160To conclude this historical insight, it should be emphasized that the Latvian Musicians’ Society was able to adapt to different circumstances and transform into new forms of work, which substantiate its importance in the formation of music life of Latvia.